Novel Patient‐Centered Approach to Facilitate Same‐Day Discharge in Patients Undergoing Elective Percutaneous Coronary Intervention. Issue 4 (15th February 2018) - Amin, Amit P.; Crimmins‐Reda, Patricia; Miller, Samantha; Rahn, Brandon; Caruso, Mary; Pierce, Andrew; Dennis, Brandy; Pendegraft, Marissa; Sorensen, Katrine; Kurz, Howard I.; Lasala, John M.; Zajarias, Alan; et al.
Abstract : Background: Same‐day discharge (SDD) after elective percutaneous coronary intervention is safe, less costly, and preferred by patients, but it is usually performed in low‐risk patients, if at all. To increase the appropriate use of SDD in more complex patients, we implemented a "patient‐centered" protocol based on risk of complications at Barnes‐Jewish Hospital. Methods and Results: Our objectives were as follows: (1) to evaluate time trends in SDD; (2) to compare (a) mortality, bleeding, and acute kidney injury, (b) patient satisfaction, and (c) hospital costs by SDD versus no SDD (NSDD); and (3) to compare SDD eligibility by our patient‐centered approach versus Society for Cardiovascular Angiography and Interventions guidelines. Our patient‐centered approach was based on prospectively identifying personalized bleeding, mortality, and acute kidney injury risks, with a personalized safe contrast limit and mitigating those risks. We analyzed Barnes‐Jewish Hospital's National Cardiovascular Data Registry CathPCI Registry data from July 1, 2009 to September 30, 2015 (N=1752). SDD increased rapidly from 0% to 77% ( P <0.001), independent of radial access. Although SDD patients were comparable to NSDD patients, SDD was not associated with adverse outcomes (0% mortality, 0% bleeds, and 0.4% acute kidney injury). Patient satisfaction was high with SDD. Propensity score–adjusted costs were $7331 lower/SDD patient ( P <0.001), saving an estimated $1.8 million annually. Only 16 patients (6.95%) met the eligibility for SDD by Society for Cardiovascular Angiography and Interventions guidelines, implying our patient‐centered approach markedly increased SDD eligibility. Conclusions: With a patient‐centered approach, SDD rapidly increased and was safe in 75% of patients undergoing elective percutaneous coronary intervention, despite patient complexity. Patient satisfaction was high, and hospital costs were lower. Patient‐centered decision making to facilitate SDD is an important opportunity to improve the value of percutaneous coronary intervention.